Topologías linealmente ordenadas - Sarmiento Sarmiento, Edilberto (Revista Científica, 2006)
In this paper we . tudy the linearly ordered topologies and for' a finite set X, we find the number of maximal chains in g (X), and find upper ánd lower bounds for the number of linearly ordered topologies.